Comparison of short-term efficacy of MIS-TLIF and Endo-LIF in the treatment of single-segment degenerative lumbar diseases - Song, Zhiwei; Zhu, Weihua; Zheng, Junwen; Wu, Gang; Li, Tianqi; Huang, Aibing; Bian, Jian; Chen, Chunmao; Li, Haijun (Frontiers in Surgery, 2022)
Background: A prospective controlled study was conducted to compare the short-term clinical results and postoperative complications of minimally invasive transforaminal lumbar decompression and fusion (Minimally Invasive Surgery-transforaminal Lumbar Interbody Fusion MIS-TLIF) and percutaneous endoscope-assisted transforaminal lumbar interbody fusion (Endoscopic Lumbar Interbody Fusion Endo-LIF) in the treatment of single-segment degenerative lumbar diseases. To provide some scientific guidance for clinicians to select surgical treatment of patients with lumbar degeneration. Methods: From October 2020 to October 2021, a total of 62 patients were enrolled, including 31 patients in the MIS-TLIF group and 31 patients in the Endo-LIF group. All patients were followed up for 6 months. The two groups of patients were recorded: (1) operation time, radiation exposure time, intraoperative blood loss, bed rest time and hospital stay, (2) ODI score (The Oswestry Disability Index, ODI), low back pain VAS score (Visual Analogue Scale, VAS) and lumbar vertebra (Japanese Orthopaedic Association Scores) JOA score 1 day before operation, 1, 3, 6 days after operation, 1, 3 and 6 months after operation. 3 X-ray evaluation of lumbar fusion at the last follow-up. Results: There were significant differences in operation time, intraoperative fluoroscopy time and hospitalization cost between the two groups, the MIS-TLIF group was significantly better than the Endo-LIF group, and the intraoperative bleeding volume of the Endo-LIF group was significantly better than that of the MIS-TLIF group, but there was no significant difference in postoperative bed rest time and postoperative hospital stay. There was no significant difference in the scores of ODI, VAS and JOA between the two groups before and after operation. At the last follow-up, the fusion rate was 100% in the (MIS-TLIF) group and 100% in the (Endo-LIF) group. Conclusions: There was no significant difference in short-term clinical efficacy and safety between Endo-LIF and MIS-TLIF in the treatment of single-segment degenerative lumbar diseases, but MIS-TLIF was significantly better than Endo-LIF in terms of operation time, hospitalization cost and fluoroscopy time, and Endo-LIF was significantly better than MIS-TLIF in terms of intraoperative blood loss.